IMPLEMENTATION OF PERMENDIKBUD NUMBER 22 OF 2017 CONCERNING INTERNAL SUPERVISION UNITS IN THE MINISTRY OF EDUCATION AND CULTURE - Linjte Marpaung; Rima Ulfayanti (Law Faculty of Universitas Bandar Lampung, 2022)
The problem in this paper is how to implement Permendikbud Number 22 of 2017 Concerning The Internal Supervisory Unit at the Lampung Provincial Language Office and what are the obstacles faced in implementing this regulation. Regulation of the Minister of Education and Culture Number 22 of 2017 concerning Internal Supervisory Units has been implemented, but has not been maximized. This is because the SPI has not been involved in mentoring and reviewing the RKAKL and Financial Reports.